2003
DOI: 10.1094/pdis.2003.87.6.662
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring for Resistance of Botryotinia fuckeliana to Anilinopyrimidine, Phenylpyrrole, and Hydroxyanilide Fungicides in Switzerland

Abstract: In Switzerland, the use of phenylpyrrole, anilinopyrimidine, and hydroxyanilide fungicides for control of Botryotinia fuckeliana, causal agent of gray mold in grapes, has been restricted to one treatment per fungicide class per year as part of an anti-resistance strategy. Resistance development in B. fuckeliana was monitored from 1995 to 2001 for the anilinopyrimidine cyprodinil and the phenylpyrrole fludioxonil and from 1997 to 2001 for the hydroxyanilide fenhexamid in experimental vineyards in Richterswil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
3
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 15 publications
3
68
3
7
Order By: Relevance
“…Fenhexamid, a hydroxanilide derivative, is one of the newly developed fungicides that exhibit strong inhibitory activity against B. cinerea, owing to its ability to inhibit 3-ketoreductase in the C4-demethylation enzyme complex during ergosterol biosynthesis (Rosslenbroich et al 2000;Debieu et al 2001). Fenhexamid is used in many European countries and is considered to be an effective fungicide against B. cinerea due to its unique mode of action (Rosslenbroich et al 2000;Debieu et al 2001;Baroffio et al 2003). However, B. cinerea wild types exhibiting resistance to fenhexamid were detected shortly after its introduction (Leroux et al 2002;Baroffio et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fenhexamid, a hydroxanilide derivative, is one of the newly developed fungicides that exhibit strong inhibitory activity against B. cinerea, owing to its ability to inhibit 3-ketoreductase in the C4-demethylation enzyme complex during ergosterol biosynthesis (Rosslenbroich et al 2000;Debieu et al 2001). Fenhexamid is used in many European countries and is considered to be an effective fungicide against B. cinerea due to its unique mode of action (Rosslenbroich et al 2000;Debieu et al 2001;Baroffio et al 2003). However, B. cinerea wild types exhibiting resistance to fenhexamid were detected shortly after its introduction (Leroux et al 2002;Baroffio et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Any shift of B. cinerea toward fluazinam in vineyards has still not revealed. In 1999, firstly in Switzerland, a botryticide with novel botryticidial action was registered, the fenhexamid (Baroffio et al, 2003). Early investigations on the fenhexamid mode of action suggested that it has different mechanism from than of all other botryticides (Rosslenbroich & Stuebler, 2000).…”
Section: Managing Grey Mouldmentioning
confidence: 99%
“…Different levels of dicarboximides-resistance variously accompanied by resistance to phenylpyrrole fungicides and reduced tolerance to high osmotic pressure point to polymorphism of Daf1 and with time become evident that there are at least five classes of responsible alleles (Hilber et al, 1995;Faretra & Pollastro, 1991;Faretra & Pollastro, 1993a, 1993bVignutelli et al, 2002;Baroffio et al, 2003). Recent studies suggested that an amino acid substitution of serine for isoleucine in the second unit of tandem amino acid repeats on 86 codon of BcOS1p gene is responsible for dicarboximides resistance in the field (Oshima et al, 2002).…”
Section: Retrospective Of Botryticide Resistancementioning
confidence: 99%
See 2 more Smart Citations